Instrumen Internasional dan Peraturan Perundangan Indonesia tentang Kebebasan dan Perlindungan Beragama - M. ATHO MUDZHAR (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
This article assures that the Indonesian government has committed to uphold human rights issue after the official ratification of several national and international conventions on human rights. As well, several decrees and constitutions have been implemented. Following this, the Indonesian commitment, therefore, as argued by this article has been on the rigth track in its effort for upholding the human rights convention particularly on religion. In doing this, the Indonesian government has founded the national commission on human rights which is in charge of monitoring the implementation of human rights in Indonesia.